Examining the implementation of Culturally Responsive Teaching Materials (CRTM) of Sasak culture literature using Culturally Responsive Teaching (CRT) - Hilmiati; Heri Suwignyo; Djoko Saryono; Roekhan (Center for Humanities and Innovation Studies, 2019)
Implementing Culturally Responsive Teaching Materials (CRTM) of Sasak culture literature using Culturally Responsive Teaching (CRT) strategy enables students to connect concepts and real-life experiences on culture. This research aims to examine the implementation of Culturally Responsive Teaching Materials (CRTM) of Sasak culture literature using Culturally Responsive Teaching (CRT) strategy. This research applied pre-experimental design with a one-group pretest-posttest design. Teaching materials taught in this study are intrinsic and extrinsic elements in short stories and novels. Thirty-three Public Islamic Senior High School student in West Nusa Tenggara participated in this research. The results of the implementation test before and after treatment indicated a significant difference. The mean score of the learning outcomes before the treatment (pretest) was 51.45 and 76.82 on the posttest. This research implies the attainment of implementing Culturally Responsive Teaching Materials (CRTM) of Sasak culture literature using Culturally Responsive Teaching (CRT) strategy to the students of Islamic Senior High School.